Avant Canada : Poets, Prophets, Revolutionaries - Bök, Christian, 1966-; Betts, Gregory, 1975- (Book collections on Project MUSE., 2018)
"It's a collection of original essays and supporting creative works on an array of Canadian literary avant-garde movements from the past 50 years. Featuring 28 writers and critics in the field, it offers an overview of the past, present, and future of Canadian avant-garde writing. It's complete survey of contemporary avant-garde activity in Canada. It explores the intersection of Canadian avant-gardisms and Indigenous decolonization. Finally, it discusses controversial topics such as the relationship between Canadian and Indigenous literature, cultural appropriation, gender, and the Conceptual Writing movement."--